Двое на краю света: [роман] / Татьяна Алюшина - Алюшина Татьяна Александровна (Еще раз про любовь, 2018)
Экземпляры: (20181004) / Инвентарный номер: / Цена: 105.35 / Сис.шифр: Р2 / Авт.знак: А 59 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6